La Oralidad, los ecos en el Tiempo - Robinson Echevarría, Vicente (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The oral tradition is deeply rooted in the country, the monumental work of religions coming from Africa were transmitted through orality. Starting from word, people leave their witness that passed down from generation to generation through time, real stories, legends, tales, and myths are transmitted and re-created even by time, receiving relevance in the popular imaginary. The community of Surgidero de Batabanó has been included in this practice. There are several stories about it with central core, other fantastic based on the imagination and the popular belief. The contribution re-creates three stories that have been told in the community since the first years of the last century (XX), that have been heard in the homely silence, dur-ing the winter nights when families gather and bring out the same. The stories by Juan Oliven, la Familia Fontanel and Policarpo Sandoval are told in this manner. They originate from stories told from the local black universe, given that their characters are black people, in which they expose their misfortune, beliefs, discriminations and spoliation to which were submitted old slaves and their descendent, practices really common and discriminated in that period. Three stories are described (even though they are not the only ones in the community), we analyze the social-historical context in which they spread, the consequences of the actions described and the contribution that the same bring to the traditional, popular culture and the oral tales as community practice.